2022
DOI: 10.22463/17949831.3092
|View full text |Cite
|
Sign up to set email alerts
|

Uso de aromaterapia en gestantes: una revisión de la literatura

Abstract: Introducción: Algunas mujeres, durante su gestación pueden padecer de sintomatología molesta que interfiere con su cotidianidad, molestias como náuseas, vómitos, dolores lumbares, y fluctuaciones emocionales. Tales molestias podrían manejarse con técnicas como la aromaterapia, propendiendo por ofrecer bienestar sin posibles efectos adversos para el binomio madre e hijo. El objetivo de este artículo es identificar los beneficios que produce la aromaterapia en la gestación mediante una revisión documental. Metod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…A review study on the effects of Lavandula angustifolia EO showed it improves people's physical and emotional states when compared to non-aromatic therapies due to its effect on the limbic system by modulating N-methyl-D-aspartate and inhibiting serotonin transport and calcium channels (11). Another review that focused on the relief of common symptoms during pregnancy noted that for anxiety, stress, and poor sleep quality, the most commonly used EO was lavender, although other EOs, such as bergamot, lemon, orange, and tangerine, have also presented relaxation and mood-enhancing effects (27). An analysis of the effect of Lavandula dentata and Citrus sinensis EOs on physical, emotional, and behavioral symptoms of occupational stress in office staff identified that both EOs administered separately by inhalation through a diffuser were effective in reducing symptoms when compared to the control group (28).…”
Section: Discussionmentioning
confidence: 99%
“…A review study on the effects of Lavandula angustifolia EO showed it improves people's physical and emotional states when compared to non-aromatic therapies due to its effect on the limbic system by modulating N-methyl-D-aspartate and inhibiting serotonin transport and calcium channels (11). Another review that focused on the relief of common symptoms during pregnancy noted that for anxiety, stress, and poor sleep quality, the most commonly used EO was lavender, although other EOs, such as bergamot, lemon, orange, and tangerine, have also presented relaxation and mood-enhancing effects (27). An analysis of the effect of Lavandula dentata and Citrus sinensis EOs on physical, emotional, and behavioral symptoms of occupational stress in office staff identified that both EOs administered separately by inhalation through a diffuser were effective in reducing symptoms when compared to the control group (28).…”
Section: Discussionmentioning
confidence: 99%
“…Enfermagem Brasil 2023;22 (6):1089-1106 Foram encontrados 15 materiais, dentre artigos e livros publicados, nos quais 11 se tratam do uso da aromaterapia em gestantes no pré-natal, 1 artigo sobre o uso no pós-parto, 2 durante o trabalho de parto, e 1 na saúde da mulher em geral, não especificando o uso de pessoas grávidas. O uso do óleo essencial de Limão se mostrou eficaz em dois artigos e presente em um livro, no tratamento dessa questão, um se tratando da sua aplicação por via inalatória de maneira isolada [15] e outra em conjunto como OE de Hortelã-pimenta [16], um artigo tratou do uso isolado do OE de Hortelã-pimenta [17], outro ainda refere o uso do OE de Menta [18]. Enfermagem Brasil 2023;22 (6):1089-1106…”
Section: Métodosunclassified
“…Para Azia, além dos óleos já mencionados, foi encontrada a eficácia do uso do OE de Mandarina e Lavanda [18,19]. Todos os materiais concluíram a eficácia significativa de ambos os óleos, combinados ou não, para o tratamento de náuseas e vômitos durante o período gestacional, não sendo relatado nenhum efeito adverso causado pelo uso, tendo forte recomendação, em vista da restrição de antieméticos possíveis de prescrição para esse período.…”
Section: Quadro I -Quadro Sinóptico: Categorização Dos Artigos Seleci...unclassified
See 2 more Smart Citations